Effectiveness of Core Stability and Balance Training on Postural Control in Children with Down Syndrome: A Narrative Review - Bryan V. Catama; Dorothy D. Silva; Marlon Y. Palbusa (Journal of Anthropology of Sport and Physical Education)
Children with Down syndrome (DS) often experience reduced muscle tone, joint instability, and coordination challenges, which can affect their balance, movement, and physical independence. This narrative review examines the effectiveness of core stability and balance training in improving postural control. A literature search of EBSCOhost, ProQuest, and Google Scholar identified randomized controlled trials (RCTs) following PRISMA guidelines. Findings indicate that while both interventions enhance stability, core stability training leads to greater improvements in trunk control and neuromuscular coordination, resulting in superior reductions in anteroposterior and mediolateral sway. Balance training supports functional adaptation but may be less effective in activating deep postural muscles. However, variations in study protocols, intervention durations, and outcome measures present challenges in determining the most effective rehabilitation strategy. While emerging evidence suggests that combining approaches could further optimize results, questions remain about long-term retention and real-world implementation. Future research should explore structured, hybrid interventions that maximize postural improvements and functional mobility for children with DS. Identifying the most effective rehabilitation model could transform therapy programs and significantly enhance their quality of life.